Putting piezoelectric sensors into Fano resonances - Mengting Wang; Jianqiu Huang; Qing-An Huang (Microsystems & Nanoengineering)
Abstract Piezoelectric resonance sensors are essential to many diverse applications associated with chemical and biological sensing. In general, they rely on continuously detecting the resonant frequency shift of piezoelectric resonators due to analytes accreting on their surfaces in vacuum, gas or fluid. Resolving the small analyte changes requires the resonators with a high quality factor. Here, we propose theoretically and demonstrate experimentally a scheme using a physics concept, i.e., a Fano resonance, to enhance the quality factor rather than optimizing the structure and material of the resonator itself though these are important. The Fano resonance arises due to the interference between a discrete mode and a continuum of modes, leading to the asymmetric and steep dispersion. In our scheme, the as-fabricated piezoelectric sensors are put into the Fano resonance by connecting an external shunt capacitor to them. As a verification case, one-port surface acoustic wave (SAW) resonators on LiNbO3 substrate, incorporating a composite of polymethyl methacrylate (PMMA) and graphene oxide (GO) for humidity sensing, have been fabricated and characterized. We enhance the quality factor by up to a factor of about 8, from 929 for the as-fabricated sensor to 7682 for that with the external shunt capacitor. Our results pave the way for the practical development of piezoelectric resonance sensors with high quality factor.